INFLUENCE OF DIFFERENT FEED ON WEEKLY BODY WEIGHT AND MORPHOMETRIC TRAITS OF NIGERIAN GOATS - NEGEDU EO; MALLAM I (Innovare Journal of Agricultural Sciences, 2025)
Objective: The objective of the experiment was to study the influence of different feed on weekly body weight (BW) and morphometric traits of Nigerian goats Methods: A total of 36 weaner goats of two breeds (West African dwarf, n=18; 9 males + 9 females) and Red Sokoto goats, n=18; 9 males +9 females) of about 3–4 months of age were used for the experiment and the treatments comprised of three diets group (100% Digitaria smutsii [DS], 50% DS+50% Groundnut haulm [GH], and 50% DS+50% CH). Data collected were BW, body length, withers height, chest girth (CG), chest depth (CD), rump height, cannon circumference (CC), chest width (CW), hind leg length (HL), fore leg length (FL), and ear length (EL). The data on BW and morphometric were subjected to analysis of variance to test the fixed effect of feed on BW and morphometric traits using Statistix Analytical software, file version 8.0. Significant differences among the means were separated using Duncan’s Multiple Range Test. Results: The results indicated that goats fed 50% DS+50% CH diet had significant (p<0.05) higher values for all the parameters with significant differences in all 8 weeks of the experiment. At week 1, goats fed 50% DS+50% CH had significantly (p<0.05) higher BW compared to those fed 100% DS and 50% DS+50% GH. At week 2, those fed 50% DS+50% CH had higher BW, CG, CC, CW, HL, FL, and EL compared to those fed 100% DS and 50%DS+50% GH. The results also showed that those fed 50% DS+50% CH had significantly (p<0.05) higher BW at weeks 3, 4, and 5 and CD at weeks 6 and 7. Similarly, those fed 50% DS+50% CH had significantly (p<0.05) higher BW and CD at week 8. Conclusion: The goats fed 50% DS+50% CH feed not only gained more weight but also exhibited better morphometric traits, indicating improved feed efficiency and nutrient utilization. This implies that goat farmers in the study area should consider implementing a feed that includes 50% DS+50% CH to maximize growth performance in their herds and feeding of goats with GHs and cowpea husk are beneficial and does not negatively affect the BW and morphometric traits of Nigerian goats.